On the Nature of Quantum Dynamical Variables - Johnston, James R. (Cosmos and History: The Journal of Natural and Social Philosophy, 2015)
An elementary review of the origin of quantum theory, with focus on the nature of the quantum dynamic variables, reveals the essential wave-likeness of quantum dynamics. The introduction of the concept of point-particle entities resulted from over-use of classical perspectives, and an issue of language: conflation of the concepts of point-particle localization, and discreteness of quantum detections. Keeping in mind the distinction between point-localization and discreteness of quantum exchange, it is clear that there is no experimental evidence for point-localization. A simple review of the origin of quantum theory, and review of several experiments designed to explore "wave-particle duality" and "complementarity" support this perspective. <!--[if gte mso 9]> Normal 0 false false false EN-AU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->